Development of a fluorescent scaffold by utilizing quercetin template for selective detection of Hg 2+ : Experimental and theoretical studies along with live cell imaging - Vishnu S; Maity, Sibaprasad; Maity, Annada C; Kumar, Malavika S; Dolai, Malay; Nag, Anish; Bylappa, Yatheesharadhya; Dutta, Gorachand; Mukherjee, Bimalendu; Kumar Das, Avijit (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2024)
Quercetin is an important antioxidant with high bioactivity and it has been used as SARS-CoV-2 inhibitor significantly. Quercetin, one of the most abundant flavonoids in nature, has been in the spot of numerous experimental and theoretical studies in the past decade due to its great biological and medicinal importance. But there have been limited instances of employing quercetin and its derivatives as a fluorescent framework for specific detection of various cations and anions in the chemosensing field. Therefore, we have developed a novel chemosensor based on quercetin coupled benzyl ethers (QBE) for selective detection of Hg with "naked-eye" colorimetric and "turn-on" fluorometric response. Initially QBE itself exhibited very weak fluorescence with low quantum yield (Φ = 0.009) due to operating photoinduced electron transfer (PET) and inhibition of excited state intramolecular proton transfer (ESIPT) as well as intramolecular charge transfer (ICT) within the molecule. But in presence of Hg , QBE showed a sharp increase in fluorescence intensity by 18-fold at wavelength 444 nm with high quantum yield (Φ = 0.159) for the chelation-enhanced fluorescence (CHEF) with coordination of Hg , which hampers PET within the molecule. The strong binding affinity of QBE towards Hg has been proved by lower detection limit at 8.47 µM and high binding constant value as 2 × 10 M . The binding mechanism has been verified by DFT study, Cyclic voltammograms and Jobs plot analysis. For the practical application, the binding selectivity of QBE with Hg has been capitalized in physiological medium to detect intracellular Hg levels in living plant tissue by using green gram seeds. Thus, employing QBE as a fluorescent chemosensor for the specific identification of Hg will pave the way for a novel approach to simplifying the creation of various chemosensors based on quercetin backbone for the precise detection of various biologically significant analytes.